Assessing the satisfaction of health professionals towards the introduction of Maathru Samman pants for normal delivery in the labour room: A multi-site mixed method study from India - Venkatashiva B. Reddy; Sirisha Pulla; Anushree Patil; Archana Bhosale; Deepti Tandon; Madhur Verma; Noorin Bhimani; Priti Gupta; Pradeep Aggarwal; Rakesh Kakkar; Star Pala; Wansalan Karu Shullai (PLoS ONE, 2025)
Introduction Healthcare professionals play a crucial role in the entire childbirth process. In this study, we studied healthcare workers’ response, satisfaction, and demand to use of Maathru Samaan Pants by pregnant women during normal labour. Methodology A cross-sectional, mixed-method study was carried in the year of 2023–2024. The study was carried out in four different regions of India. The health care professionals involved in normal delivery where pregnant women used Maathru Samman Pants, were enrolled in the study total of 20 doctors and 39 nurses were studied using a quantitative questionnaire. For the qualitative component, a total of 14 doctors and 16 nurses’ in-depth interviews were conducted. Six FDGs with 29 supporting staff was conducted. Results Of the total of 59 healthcare professionals majority of respondents were female, 51 (86.4), and the age range was evenly distributed, with 22(37.3), 21–30 years, 20(33.9), 31–40 years, and 15 (25.4) over 40 years. The majority, 49(83.1), felt that respectful maternity care was extremely important. Most health care staff agreed or strongly agreed that the MSP helped cover their body 58(98.3). A majority found the MSP saved time by preventing dressing/undressing hassle 53(90), and helped with movement before delivery 48 (81.4). A majority, 57 (96.61), agree that the introduction of MSP is a beneficial step towards respectful maternity care. Privacy in both examination and labour rooms is rated highly, with 100% satisfaction across all regions. Most staff support continuing MSP use, 56 (94.91). Some hospitals require additional laundry services or equipment 10 (16.95) or manpower for washing 5 (8.45). Key Themes identified during in-depth interviews and FDGs were comfort, design, acceptability, demand, past experiences, challenges, advantages, funds, reuse, and additional requirements for implementing MSP. Conclusion The successful integration of MSPs into healthcare settings can drive innovation and improvements, highlighting India’s leadership in advancing maternal health initiatives.